Color and rehydration characteristics of natural red colorant of foam mat dried Hibiscus sabdariffa L. powder - Tan, Suet Lin; Sulaiman, Rabiha (Taylor & Francis, 2019)
This research was aimed to develop natural red colorant powder from Hibiscus sabdariffa L. fruit using foam mat drying. Egg albumen (EA) at different concentrations (5–20% w/w) was used as a foaming agent, and samples were whipped for 10 minutes. The samples were hot air dried at 50°C for 6 hours. Effect of EA concentration on the foam properties and physicochemical properties of the powders were analyzed. In addition, the effect of temperatures (10–80°C) on color and rehydration characteristics of rehydrated powders were studied. The result showed that 15% EA concentration of foam mat dried H. sabdariffa L. powder has good quality characteristics.